A Comparative Study of National Laws Dealing with Terrorism in Broad and Narrow Senses, and their Implications for Civil Liberties, especially in the US and Pakistan - Hameed , Usman; qaiser, khushbakht; Qaiser, Zarfishan (Journal of Peace, Development and Communication, 2023)
National strategies to combat terrorism differ from state to state relative to their capacity and general principles of the national justice system. For this reason, some states implement broad definitions of terrorism authorizing preventive action, even so no crime is committed. In contrast, there are states which adopt narrow definitions of terrorism to safeguard due process rights of the suspects. While this approach may be more humane, it undermines the ability of states to act in anticipation of a terrorist attack. Clearly, the emphasis of the former strategy is to preserve national security even at the cost of civil liberties. In reverse, the latter approach aims at preserving civil liberties despite the threat of terrorism. Recently, the Supreme Court of Pakistan has re-defined terrorism to narrow down its scope, making it applicable to those acts only which are motivated to coerce a government or intimidate a civilian population to advance a religious, sectarian and ethnic objective. In furtherance of the new interpretation, these courts will be trying only most serious cases, such as those involving attacks on state infrastructure or state personnel. Apart from these, all other acts will be deemed regular crimes for want of motive to commit terrorism. This article will elucidate whether states driven by national security concerns define the word terrorism broadly criminalizing even the preparatory acts, such as, making donation to the charitable arm of a designated entity. And which aspects regarding the above provides a narrow approach.